Two drafts of "Ang Dapat Mabatid ng mga Tagalog" - Dumol, Paul A. (Journal of Philippine local history and heritage, 2017)
If Bonifacio's "Ang dapat mabatid ng mga tagalog" is compared with its Spanish translation in Retana's Archivo del bibliofilo filipino, it can be immediately concluded that the Spanish translation must have been made from a different version of Bonifacio's essay than that usually found in anthologies and collections. The Spanish translation was made from the version published in Kalayaan, the newspaper of the Katipunan; the Kalayaan Kalayaan, the newspaper of the Katupunan; the Kalayaan version is probably a later version of what is popularly known as Bonifacio's essay. In this article, the two versions are compared, and additions and alterations to and omissions from the earlier version are identified. The reasons for the changes from the earlier version to the later versions are speculated on.